Bibliometric analysis of Crohn's disease in children, 2014–2024 - Yanjing Zhu; Yanjing Zhu; Yunhong Ma; Zhengjiu Cui; Yueli Pan; Juanjuan Diao (Frontiers in Pediatrics)
BackgroundIn recent years, the incidence of Crohn's disease has risen significantly in the pediatric population, and its prolongation has had a major impact on children's physical and mental health as well as on the quality of life of their families, and has therefore received extensive attention from scholars around the world. A large number of articles have been published on Crohn's disease in children; however, there is still a lack of studies that use visualization methods for bibliometric analysis of relevant literature. The purpose of this paper is to statistically analyze the published literature in the field of Crohn's disease in children in order to help in the future diagnosis and treatment of Crohn's disease in children.MethodsLiterature meeting the inclusion criteria was screened from the Web of Science Core Collection database. Literature was visualized and analyzed by author, country, institution, journal, reference, and keyword using Citespace (6.2.R4) and VOSviewer (1.6.18).ResultsA total of 3,177 eligible publications were included. There is an overall increasing trend in the number of annual publications.Turner, Dan published the most number of articles with 78 and has a high impact in the field of CD. The most cited author was Levine, A. Among countries and institutions, the United States and Tel Aviv University had the highest number of publications. The journal with the most publications is Journal Of Pediatric Gastroenterology And Nutrition. The most co-cited journal was Inflammatory Bowel Diseases. The most cited document was ESPGHAN Revised Porto Criteria for the Diagnosis of Inflammatory Bowel Disease in Children and Adolescents, and the most cited document with the highest outbreak intensity was The Medical Management of Paediatric Crohn's Disease: an ECCO-ESPGHAN Guideline Update.The most frequent keyword was “inflammatory bowel disease”.ConclusionThis study provides a visual summary of information for the field of pediatric Crohn's disease and contributes to international collaboration to promote research in the field of pediatric Crohn's disease.